(untitled) (Research, Society and Development, 2020)
A Cannabis sativa plant, popularly known as marijuana, has about 400 substances, among these substances, 60 different types of cannabinoids, of which two are highlighted by their therapy: tetrahydrocannabinol (THC) and cannabidiol (CBD). Alzheimer’s disease or CBD works with impact or inflammation, increased oxygen and declined brain cells. The aim of this work was to explain how to use cannabidiol compound in the treatment of Alzheimer’s disease, changing the feasibility of legalizing its use. The study was developed through a bibliographic review, in which most scientific articles and books were consulted and analyzed in relation to the theme. With a search of the collected material, it was possible to observe that the pharmacological treatment of AD can be defined by specific therapies, prophylactic approach, symptomatic treatment and complementary therapy.